Work status of 5 MeV 300 kW electron accelerator - Auslender, V.L.; Chernov, K.N.; Cheskidov, V.G.; Factorovich, B.L.; Gorbunov, V.A.; Gornakov, I.V.; Kazarezov, I.V.; Korobejnikov, M.V.; Kuznetsov, G.I.; Lukin, A.N.; Makarov, I.G.; Maksimov, S.A.; et al. (Вопросы атомной науки и техники, 2006)
Design work has been completed for the accelerating structure of high-power electron accelerator with 5 MeV,
300 kW, 176 MHz parameters. The structure is being produced in BINP workshop. The paper presents the design of
the accelerating structure which consists of a chain of coaxial cavities, and block diagram of experimental
workbench. Structure of the main accelerator blocks and their degree of fabrication are viewed. Закончены проектные работы по ускоряющей структуре мощного электронного ускорителя 5 МэВ,
300 кВт, 176 МГц и ведется ее изготовление в опытном производстве Института. Дается описание
конструкции ускоряющей структуры, состоящей из цепочки связанных коаксиальных резонаторов.
Приводится блок-схема испытательного стенда, рассматривается устройство отдельных узлов ускорителя и
состояние их готовности. Закінчено проектні роботи із прискорювальної структури потужного електронного прискорювача 5 МеВ,
300 кВт, 176 МГц і ведеться її виготовлення в дослідному виробництві інституту. Дається опис конструкції
прискорювальної структури, що складається з ланцюжка зв'язаних коаксіальних резонаторів. Приводиться
блок-схема іспитового стенда, розглядається будова окремих вузлів прискорювача і стан їх готовності.